The Cinema of Muhammad Malas Visions of a Syrian Auteur - Alkassim, Samirah (Palgrave Studies in Arab Cinema, 2018)
This book provides an in-depth and intimate study of the cinema of Muhammad Malas. One of the well-known auteurs of Arab and Syrian cinema, Malas's distinctive cinematic project has always confronted the social and political issues of his time. From feature films Dreams of the City, The Night, Bab al Maqam (Passion), and Ladder to Damascus to documentaries such as The Dream and Aleppo: Maqamat of Pleasure, Malas's films challenge and explore Arab culture and history. Archival images run through the chapters of this book which combines insightful interviews with excerpts from Malas's literary works and critical explorations of his cinematic style and thematic concerns. The book concludes with Malas's own words, sharing the treatment of his film project Cinema al-Dunya.